DEVELOPMENT OF A SURROUNDING ENVIRONMENT BASED LEARNING BOOK FOR STUDENTS AT SDN PURWOREJO 03 SANANKULON - Merry Aprianti Karina D; Desy Anindia Rosyida; Adin Fauzi (JOSAR (Journal of Students Academic Research), 2023)
The objectives to be achieved in this research are to analyze the Feasibility of the Environment-Based Kewan Lan Wit-Witan Javanese Language Support Book at SDN Purworejo 03 Sanankulon Blitar and to analyze the Effectiveness of the Environment-Based Kewan Lan Wit-Witan Javanese Language Support Book at SDN Purworejo 03 Sanankulon Blitar. This research is included in development research which uses a Research and Development (R&D) approach. This development research is longitudinal (gradually) to develop a new product or improve an existing product and test its effectiveness so that it can function in the wider community. The results of the research are environment-based interactive learning media about animals and plants (Kelantan) by material experts considered appropriate with a percentage of 86.25% media experts rated "appropriate" with a percentage of 85%, and linguists rated "appropriate" with a percentage of 88.60%. Then The level of readability of interactive learning media based on the surrounding environment about animals and plants (Kelantan) by material students is considered very feasible with a percentage of 90%. Keywords: Javanese; Kewan; Wit-Witan; Supporting Books, Environment